ASPEK SEMANTIK PADA GRAFITI BAK TRUK DI REST AREA PENGGUNG KOTA CIREBON SERTA IMPLIKASINYA BAGI PERKULIAHAN - Veni Nurpadillah; Heru Susanto; Dian Aristia (CAKRAWALA LINGUISTA, 2021)
This study examines the semantic meaning of truck bed graffiti on. This research uses descriptive qualitative analysis method. Based on the type of semantic meaning, the graffiti on the back of the truck is dominated by lexical meanings. Based on the presence or absence of referentials, the graffiti on the back of the truck is dominated by referential meanings. Based on the absence of taste values, the graffiti on the back of the truck is dominated by the type of denotative meaning. Based on the determination of the meaning, the graffiti on the back of the truck in the Penggung Rest Area in Cirebon City is dominated by the type of meaning of the word. Based on the relationship between the meaning of one word and another, the graffiti on the back of the truck is dominated by the type of conceptual meaning.